2022
DOI: 10.3389/fncel.2022.843069
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation as the Underlying Mechanism of Postoperative Cognitive Dysfunction and Therapeutic Strategies

Abstract: Postoperative cognitive dysfunction (POCD) is a common neurological complication following surgery and general anesthesia, especially in elderly patients. Severe cases delay patient discharge, affect the patient’s quality of life after surgery, and are heavy burdens to society. In addition, as the population ages, surgery is increasingly used for older patients and those with higher prevalences of complications. This trend presents a huge challenge to the current healthcare system. Although studies on POCD are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 178 publications
(183 reference statements)
0
43
0
Order By: Relevance
“…Presently, there are several hypotheses about the pathogenesis of POCD, which are related to inflammation of the central nervous system, nerve cell apoptosis, dysfunction of the cholinergic nervous system, and oxidative stress injury. However, inflammation of the nervous system still plays an important role in the development of POCD [ 16 , 32 , 33 ]. According to our previous study, microRNA-221-3p could target IRF2 of astrocytes to increase IFN-α expression and regulate nervous system inflammation [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Presently, there are several hypotheses about the pathogenesis of POCD, which are related to inflammation of the central nervous system, nerve cell apoptosis, dysfunction of the cholinergic nervous system, and oxidative stress injury. However, inflammation of the nervous system still plays an important role in the development of POCD [ 16 , 32 , 33 ]. According to our previous study, microRNA-221-3p could target IRF2 of astrocytes to increase IFN-α expression and regulate nervous system inflammation [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Massive evidence showed that major surgeries could induce a widespread systemic inflammatory response, and multiple biomarkers of neuro-inflammatory response were widely observed to have an association to the pathophysiological changes underpinning POCD and cognitive deficits in clinical studies [ 4 , 5 ]. This conclusion was verified in multiple surgery rodent models in terms of its mechanism, showing that the upregulation of pro-inflammatory cytokines and inflammatory mediators in the central nervous system (CNS) could cause obvious cognitive impairment in animals, and that it could be blocked by anti-inflammatory agents [ 6 , 7 , 8 ]. Inflammation leads to oxidative stress, contributes to mitochondrial dysfunction [ 9 , 10 , 11 , 12 ], and induces a variety of metabolic disorders, such as iron metabolism disorders.…”
Section: Introductionmentioning
confidence: 95%
“…In this study, we used molecular docking stimulation to identify the binding ability between bioactive components of Xingnao Kaiqiao Pill and key targets encoded by hub genes. According to Figure 9 and According to the universally recognized pathogenesis, PND can be considered as a neuroinflammation disease (Subramaniyan and Terrando, 2019;Li et al, 2022). It has been found that there is a close connection between the nervous system and the immune system, and inhibiting the expression level of inflammatory factors or suppressing the immune response can reduce the symptoms of PND or the occurrence of PND (Mu et al, 2015).…”
Section: Molecular Docking Verificationmentioning
confidence: 99%